Dampak Relokasi Pesantren Al-Khairiyah Tahun 1978 (Suatu Kajian Historis) - Rahayu Permana (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
This research is based on concern about the study of Islamic boarding schools in the Cilegon area, which has a fairly long historical span, namely the Al-Khairiyah Islamic boarding school in 1925 founded by KH. Syamun as a clerical and military figure who had a lot of struggle in the Banten region. pesantren which is KH. Syam'un was established as an Islamic educational institution that aims to explore the knowledge of Islam by emphasizing the importance of morality and Islamic teaching experience in living in a society. Besides that pesantren education is based on the spirit of ‘living religion‘ which is reflected in all aspects of daily Islamic boarding school life. Islamic boarding school studies are so important to express through local historical approaches that are rich in sources and information. For this reason, it is necessary to approach the relevant sources to be studied more deeply, to reveal an event in the past. The study aimed to determine the impact of al-Khairiyah's displacement in 1978. Data collection was purposive sampling and snowball, carried out through interviews, observation, and documentation studies. In the process of working the data is analyzed using the Miles and Huberman models through the stages of data collection, data reduction, data display, and drawing conclusions about the reality on the ground that are natural and actual in a comprehensive and intact manner described. Given the 1974 expansion of PT. Krakatau Steel, the relocation of old pesantren in new places has resulted in many significant changes, both from the social, economic, and cultural cultures of the people that have been built since a long time ago. Nevertheless the Al-Khairiyah Islamic boarding school tried to maintain its pesantren tradition in its entirety and was consistent with its goal of fostering a generation that was reliable to be prepared to fill independence.